Penerapan Terapi Zikir untuk Mengurangi Frekuensi Halusinasi Pendengaran pada Pasien dengan Skizofrenia di Wilayah Puskesmas Sindangkasih Kabupaten Ciamis - Dede Wahyudi; Peni Cahyati; Iwan Somantri; Asep Riyana (Universitas Galuh, 2023)
The pervalence rate of riskesdas 2018 results shows that mental disorders in Indonesia are 6.7 permil household. In the West Java area, there were 5.0 permil households, in Ciamis Regency there were 6.80 permil households and in Sindangkasih District there were 76 cases with diagnosis of a schizophrenia. Schizophrenia is a type of severe mental disorder characterized by the onset of hallucinations, delusions, disturbances in thought processes, speech, disturbances in behavior as well as inappropriate emotions. Auditory hallucinations are a type of hallucination that often appears in patients with schizophrenia, and hallucinations are a loss of human ability to distinguish internal stimuli and external stimuli. This paper focuses on the management of hallucinations with one of the non-pharmacological therapies in the form of the application of zikir therapy. Meanwhile, the purposes of this study are to determine the application of zikir therapy and to determine the results of the application of zikir therapy to reduce the frequency of auditory hallucinations in patients with schizophrenia. This research uses a qualitative descriptive method with a case study approach, and was carried out from April 12 to April 15 2022. The results of the study found the same characteristics of auditory hallucinations, where both clients had hallucinations that still appeared but both were able to carry out activities especially worshipping prayers 5 times. The application of zikir therapy is given every time a meeting with the client and is recommended to be carried out every after prayer 5 times and when hallucinations appear. It was found that both clients experienced a decrease in the frequency of hallucinations. Advice for families to always support the implementation of zikir therapy on clients after completing prayers 5 times for puskesmas to always make regular visits to people with schizophrenia.